Perancangan Antarmuka dan Fitur Training Management system (TMS): Studi Kasus Divisi Corporate University PT XYZ - Iswara Maharani; Oktavia Hadi Putra, Panca (The Indonesian Journal of Computer Science, 2025)
This study addresses the fragmented learning systems at PT XYZ, where separate and manually managed platforms result in inefficient training documentation. With an annual learning volume of 156,018 training hours and a rise in mandays from 9.4 (2019) to 12.8 (2023), the inefficiencies significantly impact training management. The research aims to design the interface and features of a Training Management System (TMS) for PT XYZ using a Systematic Literature Review (SLR) and a user-centered design (UCD) approach to align with user needs. A mixed-methods approach combines qualitative and quantitative techniques, including interviews, pre-questionnaires, usability tests, feedback sessions, and Subject Matter Expert inputs. Evaluation results show an average score of 4.29 out of 5, reflecting user satisfaction with the system's functionality, efficiency, and reliability. Effective implementation of the TMS is expected to improve training quality, support human resource development, and help achieve strategic corporate objectives.